Damage analysis of composite–aluminium adhesively-bonded single-lap joints - Ribeiro, T.E.A. (2016)
Adhesive bonding is used to fabricate structures of complex shape that could not be manufactured in one piece. In many high performance structures, joints between composite materials with other light metals such as aluminium are required for structural optimization. This work numerically and experimentally addresses adhesive joints between aluminium and carbon–epoxy composites, considering different adhesives and value of overlap length (LO). Numerically, the Finite Element Method (FEM) coupled with cohesive zone models (CZM) is used to perform a detailed stress analysis that enables the comparison between different planes in the joint and LO values. A damage analysis during damage and crack growth is also considered to fully describe the failure process. The use of the proposed numerical technique enables predicting the joint strength and creating a simple and rapid methodology that can be used in the design of hybrid structures, e.g. in the selection of the joint geometry and adhesive. The joints’ strength and failure modes were highly dependent on the adhesive, and this behaviour was successfully modelled numerically. Using a brittle adhesive resulted in a negligible maximum load (Pm) improvement with LO. The joints bonded with the ductile adhesive showed a nearly linear improvement of Pm with LO.